Layperson's knowledge and perceptions of irritable bowel syndrome as potential barriers to care. (30th January 2018) - Sherwin, LeeAnne B.
Abstract: Aims: The aim of this study was to describe the layperson's knowledge and perceptions regarding the aetiology, pathogenesis, prevalence, medical evaluation, diagnosis and treatment of irritable bowel syndrome. Background: Diagnosis acceptance and adherence to treatment is influenced by the views of the patient's social networks. Little is known how these networks influence those with irritable bowel syndrome. Design: Cross‐sectional study of two‐hundred four laypersons, ages 18–80 years without an irritable bowel syndrome diagnosis. Methods: Data were collected May 2016–March 2017. Laypersons without a diagnosis of IBS self‐reported their knowledge and perceptions about IBS. Results/findings: Participants were able to identify many symptoms associated with irritable bowel syndrome however held misconceptions regarding the development of irritable bowel syndrome as noted by the endorsement of genetics, environment and diet or alcohol/smoking behaviours as specific causes. Further misconceptions held included the belief that irritable bowel syndrome was associated with an increased risk for the development of colon cancer and inflammatory bowel disease. Contrary to current guidelines, many thought a gastroenterologist was the only person appropriate to diagnose irritable bowel syndrome and objective testing, such as colonoscopy, was necessary to establish a diagnosis. Conclusion: Laypersons have an understanding of the symptoms associated with IBS; however, hold numerous misconceptions regarding the aetiology, role of the healthcare provider, necessary testing and risks associated with irritable bowel syndrome. These misconceptions are inconsistent with current guidelines and practices. Establishing partnerships and educating social networks in addition to patients may enhance outcomes for those with IBS.